APLIKASI TEKNOLOGI DIGESTER UNTUK PENGOLAHAN HUMAN MANURE, SAMPAH ORGANIK DAN LIMBAH CAIR DOMESTIK DI ASRAMA MAHASISWA KOTA BANJARBARU KALIMANTAN SELATAN - Achmad Kusairi Samlawi; Yulian Firmana Arifin; Lailan Ni'mah (Universitas Lambung Mangkurat, 2016)
Student dormitory is one of the facilities provided as a means of support for the students in their studies in Universities. Because many students who come from outside the region where the study was held. Dormitory students have an important role in supporting the successful development in the field of education as well as business opportunities to boost the economy of the people who live around educational institutions. However on the other side where the hostel will generate waste, among others, feces and urine, organic and inorganic garbage and domestic waste which if not managed properly could potentially cause health problems, and aesthetics. The problems that have been faced by managers and occupants of a student dormitory in the Kelurahan Sungai Besar, Kecamatan Banjarbaru Selatan, Banjarbaru City is the lack of knowledge of how the processing waste human manure, organic waste and domestic waste water so it does not pollute the surrounding environment and at the same time converting the processed organic waste into a resource new energy, namely biogas and compost.Digester technology applications will generate a set of tools Human waste processing manure, organic waste and domestic waste. This technology is the processing of organic material anaerobic digester technology in the form of organic waste that the waste that comes out of the digester safely discharged into the environment. Aside from being a waste treatment plant, the solution can also produce biogas to biogas formed later expected to be utilized as a fuel substitute for LPG and fuel Generator Set (Genset) as a substitute fuel (gasoline) in addition produce a byproduct of compost were also no less economic value. Inside the digester hydrolysis and fermentation process occurs, phase Acetogenesis and methanogenesis phase of organic waste into biogas and its byproducts are composted. The process takes 20-30 days. Wastewater digester output of the reactor is no longer harmful to humans, the environment and other living organisms that are not harmful to the environment if disposed of.